MEMBANGUN MOTIVASI SISWA YANG MAMPU MEMANAJEMEN WAKTU DENGAN BAIK - Hanum Puspa Dhiani; Arif Siaha Widodo; Nurilah Hanum; Mutmainnah Mutmainnah; Ahmad Dimyati (LPPM Universitas Pamulang, 2020)
The development of technology and information that was increasingly fast and sophisticated brought positive and negative impacts to the millennial generation who were already fluent in using technology. This certainly would affect the millennial generation’s motivation to learn and time management which the majority of those generation are students. In order to make the students manage the time well, strategies were needed to find out the way for students who able to manage time well and to increase student motivation in carrying out their activities as students while utilizing time productively. Therefore, we hold Community Service (PKM) with the theme